Uniform dispersion of SiC in Yb-filled skutterudite nanocomposites with high thermoelectric and mechanical performance. (15th March 2019) - Zhou, Zhenxing; Li, Jianlin; Fan, Yuchi; Zhang, Qihao; Lu, Xiaofang; Fan, Shengjie; Kikuchi, Keiko; Nomura, Naoyuki; Kawasaki, Akira; Wang, Lianjun; Jiang, Wan
Abstract: Although filled skutterudites are very promising thermoelectric (TE) materials at intermediate temperature, most of the high-performance skutterudites reported are multiple-filled materials that tend to have poor stability and machinability. Here, we successfully fabricate single-filled skutterudite based composites with uniformly dispersed β-SiC nanoparticles via cryogenic grinding and spark plasma sintering. The nanocomposites show not only increased Seebeck coefficient owing to a possible energy filtering effect, but also reduced lattice thermal conductivity through enhanced phonon scattering. A maximum ZT value of 1.42 at 850 K with greatly improved mechanical properties is achieved, which is very attractive for the application in TE devices. Graphical abstract: Unlabelled Image